Working women of Manila in the nineteenth century - Camagay, Ma. Luisa T. (The University of the Philippines Press, 2024)
The work documents the life of gainfully employed women in the 19th century. Seven occupations of women were studied, namely, the cigarreras (tobacco factory workers), the matronas titulares (licensed midwives), the maestras (teachers), the criadas (female domestic workers), the tenderas and vendadoras (store owners and vendors), the costureras and bordadoras (seamstresses and embroiderers), and the mujeres publicas (prostitutes)."--BOOK JACKET. "With women often absent or marginalized in the pages of history, the study attempts to unravel through archival sources and other non-documentary sources like literature and iconography the life of these working women. Despite the meager archival materials on women and more specifically working women, this study prides itself in having used primary sources to document working Filipino women during the Spanish period.--Back cover.